Major influence of dysfunctions of protective serum proteins on cardiometabolic risk among Turks and gender difference - Onat, Altan; Hergenc, Gulay; Can, Gunay (TURKISH SOC CARDIOLOGY, 2009)
Knowledge obtained from the Turkish Adult Risk Factor (TARF) study on higher morbidity and mortality rates compared to other populations, from coronary heart disease (CHD) among Turkish adults has been confirmed more strongly recently. This review provides insight that the dysfunctions of protective serum proteins, attaining pro-inflammatory and atherogenic features, may be attributed to atherogenic dyslipidemia, oxidative stress, and systemic inflammation associated with the high prevalence of metabolic syndrome (MetS) among Turks. The mentioned protective protein dysfunctions, firstly described in a general population to date, are high-density lipoprotein (HDL), apolipoprotein (apo) A-I, A-II, and apoC-III, apart from adiponectin. Based on published findings of the TARF study, this review discusses the role of inflammatory mediators such as elevated C-reactive protein (CRP), apoB, apoC-III, fibrinogen, and low adiponectin serum levels on cardiometabolic risks comprising MetS, type 2 diabetes, and CHD, the degree of independence of these mediators from the ATP-III-defined MetS, and the influence of sex. Moreover, it is emphasized that dysfunctions of adiponectin and protective proteins related to HDL particles increase not only cardiometabolic risk significantly but also CHD risk among half of Turkish adults in a magnitude similar to or greater than that associated with traditional risk factors. Also underlined is the observation that cigarette smoking reduces the risk in Turkish women for the development of hypertension, MetS, and diabetes by mediation of positive effects on dysfunctional apoA-I, visceral fat accumulation and, above all, CRP levels. This knowledge is of utmost importance and sheds light to authorities and those concerned on the necessity of urgent and radical modifications regarding strategies in prevention and management of cardiovascular health of middle-aged Turks.
Keywords: Apolipoproteins; cholesterol; HDL; coronary disease; inflammation; risk factors; sex factors; smoking; Cardiovascular System & Cardiology